(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to determine whether there is an Effect of Hanging Ball Training on Smash Ability in Volleyball Games in the Lampo Village Team. This study uses a quantitative approach, involving the Lampo Village Volleyball Team as the population, and 12 people as samples using total sampling. The data collection technique was carried out by providing initial smash test treatment then hanging ball training treatment and final smash test treatment to the Lampo village team. The results of this study indicate that the average value before being given hanging ball training was 10.67, and after being given hanging ball training was 15.33 so that there was an increase of 4.66.Based on the results of the test sample calculation where t count = 16.197 while t table at the 5% level with degrees of freedom (db) = n-1 = 11 is 1.796 so it can be concluded that H0 is rejected and Ha is accepted because the t count value is greater than t table, which is 16.197 > 1.796. The results of the study show that there isThe Effect of Hanging Ball Training on Smash Ability in Volleyball Games in the Lampo Village Team.